Phase 2 study of all‐oral ixazomib, cyclophosphamide and low‐dose dexamethasone for relapsed/refractory multiple myeloma. (20th November 2018) - Kumar, Shaji K.; Grzasko, Norbert; Delimpasi, Sosana; Jedrzejczak, Wieslaw W.; Grosicki, Sebastian; Kyrtsonis, Marie‐Christine; Spencer, Andrew; Gupta, Neeraj; Teng, Zhaoyang; Byrne, Catriona; Labotka, Richard; Dimopoulos, Meletios A.
Summary: There is a need for efficacious, convenient treatments with long‐term tolerability for patients with relapsed/refractory multiple myeloma (RRMM). This phase 2 study evaluated the all‐oral combination of ixazomib, cyclophosphamide and dexamethasone (ICd). Patients with RRMM received ixazomib 4 mg and cyclophosphamide 300 mg/m 2 on days 1, 8 and 15, and dexamethasone 40 mg on days 1, 8, 15 and 22 in 28‐day cycles. The primary endpoint was overall response rate (ORR). Seventy‐eight patients were enrolled (median age 63·5 years). At data cut‐off, patients had received a median of 12 treatment cycles; 31% remained on treatment. ORR was 48% [16% very good partial response or better (≥VGPR)]. ORR was 64% and 32% in patients aged ≥65 and <65 years (25% and 16% ≥VGPR), respectively. At a median follow‐up of 15·2 months, median progression‐free survival (PFS) was 14·2 months, with a trend towards better PFS in patients aged ≥65 years vs. <65 years (median 18·7 months vs. 12·0 months; hazard ratio 0·62, P = 0·14). ICd was well tolerated. The most common treatment‐emergent adverse events were diarrhoea (33%), nausea (24%), upper respiratory tract infection (24%), and thrombocytopenia (22%); 10 patients (13%) had peripheral neuropathy (one grade 3). This study is registered at ClinicalTrials.gov (NCT02046070).